Isolation of peritoneum-derived mast cells and their functional characterization with Ca2+-imaging and degranulation assays - Tsvilovskyy, Volodymyr; Solís-López, Alejandra; Wellach, Kathrin; Freichel, Marc (JoVE. Video journal, 2018)
Mast cells (MCs), as a part of the immune system, play a key role in defending the host against several pathogens and in the initiation of the allergic immune response. The activation of MCs via the cross-linking of surface IgE bound to high affinity IgE receptor (FcεRI), as well as through the stimulation of several other receptors, initiates the rise of the free intracellular Ca2+ level ([Ca2+]i) that promotes the release of inflammatory and allergic mediators. The identification of molecular constituents involved in these signaling pathways is crucial for understanding the regulation of MC function. In this article, we describe a protocol for the isolation of murine connective tissue type MCs by peritoneal lavage and cultivation of peritoneal MCs (PMCs). Cultures of MCs from various knockout mouse models by this methodology represent a useful approach to the identification of proteins involved in MC signaling pathways. In addition, we also describe a protocol for single cell Fura-2 imaging as an important technique for the quantification of Ca2+ signaling in MCs. Fluorescence-based monitoring of [Ca2+]i is a reliable and commonly used approach to study Ca2+ signaling events, including store-operated calcium entry, which is of utmost importance for MC activation. For the analysis of MC degranulation, we describe a β-hexosaminidase release assay. The amount of β-hexosaminidase released into the culture medium is considered as a degranulation marker for all three different secretory subsets described in MCs. β-hexosaminidase can easily be quantified by its reaction with a colorigenic substrate in a microtiter plate colorimetric assay. This highly reproducible technique is cost-effective and requires no specialized equipment. Overall, the provided protocol demonstrates a high yield of MCs expressing typical MC surface markers, displaying typical morphological and phenotypic features of MCs, and demonstrating highly reproducible responses to secretagogues in Ca2+-imaging and degranulation assays.
Gesehen am 13.06.2019
Im Titel ist "2+" nach "Ca" hochgestellt
Enthält auch Versuchsbeschreibung in Textform (10 Seiten)
Wissenschaftlicher Film. Deutschland. 2018
Keywords: Film